The Harmony Taste Of Bakar Batu Tradition On Papua Land - abu muslim (Center for Research and Development of Religious Literature and Heritage, 2019)
This study aims to explore and understand the religious values contained in the Bakar Batu tradition for people in the land of Papua. With a qualitative approach, this research was conducted to find religious values in the culture of society, and describe the various meanings of the community towards these values. After going through the process of interviews, observation and study of documents, this study found that the tradition of Bakar Batu, which is an indigenous culture in the land of Papua, has undergone a transformation in governance, and the purpose of its tradition. Bakar Batu, which used to be a culinary wisdom of the people in the land of Papua, transformed into one of the solvents of vengeance and wound fusion for people who had previously fought each other. Bakar Batu also functions as a medium for channeling the blessings of the Supreme Being to the community, through the hands of executors of tradition. Tolerance, mutual cooperation and mutual respect are also reflected in the noble values of the implementation of the Bakar Batu tradition in the midst of the Papuan people. Bakar Batu is now a unifying medium between indigenous Papuans, people living in Papua, and migrants. The depth and noble wisdom of the process of Bakar Batu implementation also shows the achievement of religious values that have the potential to realize shared ideals towards a land of peace in Papua. Keywords: Bakar Batu, Papua, Culinary, Harmony Taste, Tolerance